2013
DOI: 10.1155/2013/361489
|View full text |Cite
|
Sign up to set email alerts
|

Mullerian Inhibiting Substance Suppresses Proliferation and Induces Apoptosis and Autophagy in Endometriosis Cells In Vitro

Abstract: Objective. To determine the effects of Mullerian inhibiting substance (MIS) treatment on endometriosis cells through study of apoptosis and autophagy. Design. Experimental in vitro study. Setting. University research laboratory. Cell Line. CRL-7566 endometriosis cell line. This line was established from a benign ovarian cyst taken from a patient with endometriosis. Interventions. In vitro treatment with MIS. Main Outcome Measures. The main outcome measures were cellular viability, proliferation, cell-cycle arr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0
2

Year Published

2014
2014
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(13 citation statements)
references
References 20 publications
1
10
0
2
Order By: Relevance
“…We observed that NanoCOR exerted a stronger effect on EctESC cultures than in EuESC and CESC cultures (Figure ). In accordance with these findings, other studies have shown that stromal cells from endometriotic lesions are more susceptible to pharmacological treatment than the cultures of human stromal cells of eutopic endometrium [55–57]. Moreover, differences were also observed between the responses of EuESC and CESC cultures after treatment with NanoCOR, where the EuESC cultures better responded to the treatment (Figures and ).…”
Section: Discussionsupporting
confidence: 84%
“…We observed that NanoCOR exerted a stronger effect on EctESC cultures than in EuESC and CESC cultures (Figure ). In accordance with these findings, other studies have shown that stromal cells from endometriotic lesions are more susceptible to pharmacological treatment than the cultures of human stromal cells of eutopic endometrium [55–57]. Moreover, differences were also observed between the responses of EuESC and CESC cultures after treatment with NanoCOR, where the EuESC cultures better responded to the treatment (Figures and ).…”
Section: Discussionsupporting
confidence: 84%
“…The annexin V assay was used to analyze apoptosis, as previously described [ 18 ], of ESC endo and ESC cyst , which were stained with CFSE as described above before they were added to 12-well plates and cultured with irradiated Ad-MSC. After 3 days of cell culture, ESC endo and ESC cyst were harvested and resuspended in 100 μ L annexin V binding buffer (10 mM of 4-(2-hydroxyethyl)-1-piperazineethanesulfonic acid (Life technologies) + 140 mM of sodium chloride (Sigma) + 2.5 mM of calcium chloride (Sigma)).…”
Section: Methodsmentioning
confidence: 99%
“…ICAT inhibits ovarian cancer cell proliferation and invasion, by inducing cell apoptosis and arrests cell cycle progression (28). MIS/AMH inhibits cell growth and induces autophagy in gynecological cancer cell lines (29). A recent study shows that MIS/AMH-treated cells accumulated in the G 1 phase of the cell cycle and subsequently underwent apoptosis in human epithe-lial ovarian cancer cells.…”
Section: Disccutionmentioning
confidence: 99%